Attitudes, values and belief towards money: gender and working sector comparison - Sabri, Mohamad Fazli; Hayhoe, C. R.; Goh, Lay Ai (Universiti Putra Malaysia Press, 2006)
This exploratory study focused on psychology of money by gender and private versus public sector workers in Malacca. The sample consisted of 120 respondents collected through systematic sampling procedure. There were statistically significant differences between males and females in the obsession and power money attitudes. Males scored higher than females. The sectors exhibited significant differences in four money attitude (retention, power, security, and effort/ability). Government sector respondents scored higher on retention, and effort/ability than private sector workers; those in the private sector scored higher on power and security. Scores on the money values and beliefs scale were significantly different by gender but not by sector. The implication of the study showed that by exercising good habits in money-usage, positive values and attitudes towards money certainly brings well-being for their life-time.